2024
DOI: 10.1021/acs.est.3c05142
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Emission Factors: A Foundation for the Terrestrial-Atmospheric Modeling of Bacteria Aerosolized by Wildland Fires

Leda N. Kobziar,
Phinehas Lampman,
Ali Tohidi
et al.

Abstract: Wildland fire is a major global driver in the exchange of aerosols between terrestrial environments and the atmosphere. This exchange is commonly quantified using emission factors or the mass of a pollutant emitted per mass of fuel burned. However, emission factors for microbes aerosolized by fire have yet to be determined. Using bacterial cell concentrations collected on unmanned aircraft systems over forest fires in Utah, USA, we determine bacterial emission factors (BEFs) for the first time. We estimate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…74 Similarly, Kobziar et al have recently shown for the first time that large amounts of microbial biomass is emitted from wildland fires and transported long distances in air with potential health consequences to ecosystems and humans. 75…”
Section: Linkages To Climate Researchmentioning
confidence: 99%
“…74 Similarly, Kobziar et al have recently shown for the first time that large amounts of microbial biomass is emitted from wildland fires and transported long distances in air with potential health consequences to ecosystems and humans. 75…”
Section: Linkages To Climate Researchmentioning
confidence: 99%